The peep diaries : how we're learning to love watching ourselves and our neighbors - Niedzviecki, Hal, 1971- (San Francisco, CA : City Lights Books, 2009)
We have entered the age of "peep culture": a tell-all, show-all, know-all digital phenomenon that is dramatically altering notions of privacy, individuality, security, and even humanity. Peep culture is reality TV, YouTube, MySpace, Facebook, Twitter, over-the-counter spy gear, blogs, chat rooms, amateur porn, surveillance technology, and more. Core values and rights we once took for granted are rapidly being renegotiated, often without our even noticing.--From publisher description.
Introducing peep culture -- Becoming a peep (product) person -- Faking the real : everyday secrets and the rise of peep TV -- Breaking the seal : gossip, grooming and the (secret) allure of peep -- Watching the detectives watching the neighbors in the golden age of surveillance -- Escape from the castle : privacy in the age of peep -- Future peep : why no one came to my party and other semi-transparent conclusions.
Includes bibliographical references (p. 279-285) and index.
Keywords: Social interaction; Technology -- Social aspects; Privacy; Self-disclosure -- Social aspects; Blogs; Reality television programs